The insured portfolio your gateway to stress free global investments - Nolan, Erika; Crouch, Shannon; Sola, Marc-Andre.; Safari eBooks (Hoboken, N.J. : Wiley, 2010)
"It's no secret-the U.S. economy is in crisis mode, threatening everything from personal savings to our overall prosperity as a nation. Panicking is not the answer. Having a clear game plan is. In this environment, investors must protect themselves from the immense financial uncertainties they face as a saver or an investor in the 21st Century. Investors need solid information about ways to recession-proof their retirement and investment portfolios. The Insured Portfolio offers that guidance revealing the major financial threats the 21st Century Saver and Investor faces and showing them how to build a strong portfolio and protect their assets."--Resource description page.
Welcome to the 21st century : the lessons of the first decade, and the historical precedent for today's "unprecedented" crisis -- Passing the wealth baton : building a sustainable investment & savings plan to insure a solid financial future -- An age-old solution to insure your portfolio : meeting all the requirements of the real world -- Finding the right policy to meet your financial goals and secure your piece of mind -- The importance of a jurisdiction for your insured portfolio, plus our top recommendations -- Heading out into the unknown with confidence.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Portfolio management; Global Financial Crisis, 2008-2009.; Electronic books